2020
DOI: 10.2147/prbm.s266976
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Factors Associated with Suicidal Ideation in Institutionalized Patients with Schizophrenia</p>

Abstract: Purpose The shorter life expectancy and increased risk of suicide in patients with schizophrenia have been well documented. However, study outcomes on suicidality in this special population have been few to date. This study investigated the prevalence and factors associated with suicidal ideation in a population of institutionalized patients with schizophrenia. Methods Two hundred fifty-six patients with schizophrenia between the age of 18 and 65 years were randomly rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
1
1
1
Order By: Relevance
“…Additionally, high suicide attempts was found to be associated with increased suicidal ideation in people with SZ, similar to a previous study [ 68 ]. Suicide is a continuous process, and more suicide attempts may lead to more suicides [ 69 ].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, high suicide attempts was found to be associated with increased suicidal ideation in people with SZ, similar to a previous study [ 68 ]. Suicide is a continuous process, and more suicide attempts may lead to more suicides [ 69 ].…”
Section: Discussionsupporting
confidence: 89%
“…This may be because certain people are more prone to suicidal ideation and attempts owing to their loneliness, social Mena S., et al isolation, and loss of a partner and social network. This finding conflicts with that of (Chong, et al, 2020), who showed that patients who were divorced or separated had the highest prevalence of suicidal ideation.…”
Section: Relation Between Suicidal Ideation and Personal Data Among T...contrasting
confidence: 88%
“…Suicidality is a complex social phenomenon, which is closely related to sociological, psychological, and biological factors. The risk factors included demographic variables(such as younger age, male [ 10 ], and higher premorbid IQ [ 11 ]), clinical characteristics (such as chronic disease courses, younger age at onset, increased positive symptoms, decreased negative symptoms [ 12 ], insomnia symptoms [ 13 ], a greater level of insight [ 14 ] ,and fewer cognitive deficits [ 15 ]), sociological factors(such as poor social function, poor social support [ 16 , 17 ]), and psychological factors (such as emotional problems, hopelessness (16), and psychological pain [ 18 ]).…”
Section: Introductionmentioning
confidence: 99%